Employing the unemployed of Marienthal: evaluation of a guaranteed job program - Kasy, M; Lehner, L (University of Oxford, 2022)
We evaluate a guaranteed job program that was piloted, starting in October 2020, in the municipality of Gramatneusiedl in Austria. This program provided individually tailored, voluntary jobs to all long-term unemployed residents. Our evaluation is based on three estimation approaches. The first approach uses pairwise matched randomization of participants into waves for program adoption. The second approach uses a pre-registered synthetic control at the municipality level. The third approach compares program participants to observationally similar individuals in control municipalities. These different approaches allow us to separate out direct effects of program participation, anticipation effects of future participation, and municipality-level equilibrium effects.